If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(5x + 4) + 5 = 0 Reorder the terms: -6(4 + 5x) + 5 = 0 (4 * -6 + 5x * -6) + 5 = 0 (-24 + -30x) + 5 = 0 Reorder the terms: -24 + 5 + -30x = 0 Combine like terms: -24 + 5 = -19 -19 + -30x = 0 Solving -19 + -30x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -30x = 0 + 19 Combine like terms: -19 + 19 = 0 0 + -30x = 0 + 19 -30x = 0 + 19 Combine like terms: 0 + 19 = 19 -30x = 19 Divide each side by '-30'. x = -0.6333333333 Simplifying x = -0.6333333333
| 4cosx^2-2=0 | | cosx^2=0 | | 3.2-(-2.3)=3.2+2.3 | | 49t^3-49t=0 | | 3(1.2x-0.2)=6.6 | | 6x-3+10x=2 | | x(y)=z | | 3x^2-15x-108= | | (x-(-4-5i))(x-(-4+5i))=0 | | 60h=40+55h | | 10k-1=-6k-43 | | -10w-3-2.5w+20=67 | | 2x+61+4x+32=105 | | 2x+3y+3x=15 | | 13-3x-=8x+4-11x | | 5/3x-10=1/3x | | 3(x-15)-13=x+1 | | 2(24)+2y=-56 | | H=-16t^2+1000t | | f(x)=2.15(2x-4x-6) | | 2x^2+12k=-18 | | 7+3x(1-x)=5-2(3-4x) | | x(2x-2)=4 | | 5(2x-10)(x+3)=0 | | abs(5x+2)-7=-3 | | x(2x-2)=0 | | 20x-2=18-4 | | 50+6x+27=3x+86 | | h(t) = -16t2 + 32t + 40 | | 6x-10x=4 | | (5w-8)(1-w)=0 | | 6x=5x+2(x-1)-x+b |